Knowledge, Attitude and Practice of ENT Physicians Considering Thyroid Nodules During Pregnancy: A Cross-Sectional Study - Alsaeedi, MD, Bashayer; Albusairi, Shahad Albusairi; Abdulrahim, Alaa Abdulrahim; Fayez, MD, Hanaa (International Journal of Innovative Research in Medical Science, 2022)
Background: There is limited information considering the familiarity of ENT physicians toward thyroid nodules during pregnancy. Most surveys in this field were focused on the thyroid disorders and among other population. Therefore, the aim of this study was to evaluate the knowledge, attitude, and practice of ENT physicians toward thyroid nodules during pregnancy. Methodology: This is a cross-sectional study that was conducted among ENT physicians in Saudi Arabia in the period between July 2022 and September 2022. The study depended on self-reported questionnaire that was distributed using Google sheets via E- mail through the Saudi Commission for Health Specialties. The questionnaire was prepared by the researchers depending on the previous literature review. The questionnaire consisted of four sections of 24 questions considering demographic factors, knowledge, attitudes, and practices toward thyroid nodules. Results: In this study, we were able to collect data from 385 ENT physicians. Among the participants, 60.3 % of them were at 26-35 years group and 69.6 % were males. Moreover, 75.1 % of the participants were residents, 16.6 % were consultant and 8.3 % were registrars. 43.6 % of the ENT physicians had adequate knowledge considering thyroid nodules in pregnancy while 22.3 % of the participants had positive attitude toward thyroid nodules during pregnancy and 47.0 % of the ENT physicians in this study had proactive practice toward thyroid nodules in pregnancy. Age, higher scientific degree and occupation are factors that had significant on the physicians’ knowledge, attitude, and practice. Conclusion: Knowledge, attitude, and practices of ENT physicians toward thyroid nodules during pregnancy is not adequate. Needs for increasing the awareness of the ENT physicians throughout courses and campaigns is necessary.